2000
DOI: 10.1073/pnas.210391597
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of thein vivointeraction of key cell death regulators by structure-based design of second-site suppressors

Abstract: Demonstrating in vivo interaction of two important biomolecules and the relevance of the interaction to a biological process have been difficult issues in biomedical research. Here, we report the use of a homology modeling approach to establish the significance of protein interactions in governing the activation of programmed cell death in Caenorhabditis elegans. A protein interaction cascade has been postulated to mediate activation of cell death in nematodes, in which the BH3-domain-containing (Bcl-2 homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…29 While we cannot eliminate the possibility that the CED-4/CED-9 complex known to be associated with the mitochondrial membrane in the worm exists in a different oligomeric form to that described here for the E. coli-derived complex, our biochemical data for different complexes, including mutants, are consistent with the features of the protein complex characterised previously. 5,6,[8][9][10]12,15 For example, we have shown that the formation of the complex is not dependent on the presence of the CARD of CED-4, consistent with the requirement that it be free to recruit CED-3 to a trimolecular complex of CED-3/CED-4/CED-9. 7 This result agrees with other studies using yeast two-hybrid assays showing a strong interaction between CED-9 and CED-4 with its CARD deleted.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…29 While we cannot eliminate the possibility that the CED-4/CED-9 complex known to be associated with the mitochondrial membrane in the worm exists in a different oligomeric form to that described here for the E. coli-derived complex, our biochemical data for different complexes, including mutants, are consistent with the features of the protein complex characterised previously. 5,6,[8][9][10]12,15 For example, we have shown that the formation of the complex is not dependent on the presence of the CARD of CED-4, consistent with the requirement that it be free to recruit CED-3 to a trimolecular complex of CED-3/CED-4/CED-9. 7 This result agrees with other studies using yeast two-hybrid assays showing a strong interaction between CED-9 and CED-4 with its CARD deleted.…”
Section: Discussionsupporting
confidence: 78%
“…Importantly, the release of the CED-4 from the complex appeared to be dependent upon a specific interaction of the EGL-1 BH3 peptide with wild-type CED-9. A single point mutation in CED-9, substituting the highly conserved glycine at position 169 with glutamate, which has been reported to effect EGL-1 binding, 8,15 completely prevented the EGL-1 BH3 domain peptide from displacing CED-4 (Figure 3d,e). However, the ability of this mutant CED-9 to bind CED-4 was unaffected (Figure 3d), which may explain why this mutant is a more potent inhibitor of cell death 4 since it can no longer be restrained by EGL-1.…”
Section: Egl-1 Bh3 Domain Displaces Ced-4 From Ced-9mentioning
confidence: 79%
See 2 more Smart Citations
“…In animals, homozygous for a temperature-sensitive ced-9(lf) allele, the number of cell deaths observed in the germ line is nearly three times than that observed in wild-type animals. Surprisingly, however, neither egl-1(lf) mutations nor a ced-9(gf) mutation, reported to disrupt binding to EGL-1, 23,35 affects germ cell death. Thus, in the germ line, egl-1 cannot serve to integrate signals that control cell death onset.…”
Section: Egl-1-independent Cell Death In the C Elegans Germ Linementioning
confidence: 99%